2011
DOI: 10.4103/0976-237x.91793
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of various disinfectants on microbially contaminated toothbrushes due to brushing

Abstract: Aims:To evaluate the effectiveness of different disinfectant agents in decontaminating the toothbrushes, and to educate the children, parents and the community on the decontamination of toothbrushes.Materials and Methods:Fifty healthy male children in the age range of 8–11 years were enrolled. They were divided into five groups of 10 each and provided with toothbrushes and disinfectants. Instructions were given to the children and the toothbrushes were collected after brushing and cultured for the growth of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Sodium hypochlorite has been reported to be an effective disinfectant. [ 18 ] Sodium hypochlorite is used worldwide for endodontic treatment due to its highly desirable properties as a bactericidal, deodorant and tissue solvent. When NaOCl is added to water, hypochlorous acid is formed, which contains active chlorine, a strong oxidizing agent.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium hypochlorite has been reported to be an effective disinfectant. [ 18 ] Sodium hypochlorite is used worldwide for endodontic treatment due to its highly desirable properties as a bactericidal, deodorant and tissue solvent. When NaOCl is added to water, hypochlorous acid is formed, which contains active chlorine, a strong oxidizing agent.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical agents, such as cetylpyridinium chloride [11], 1.0% sodium hypochlorite, chlorhexidine, Dettol, essential oil mouthwash, and 3% hydrogen peroxide [12], have been shown to be efficacious in reducing the microbial contamination of toothbrushes. However, there is scant literature on the influence of these chemical agents on toothbrush bristle properties.…”
Section: Discussionmentioning
confidence: 99%
“…Essential oil derivates (Listerine) are chemical agents traditionally considered as trustable antiseptics and disinfectants with no secondary effects on host's oral cavity [1,6,8,9]. Listerine is a mouth rinse composed by menthol, ethanol, thymol, eucalyptol (essential oils) and methyl salicylate as active agents; previous investigations reported that this mouth rinse has wide range of disinfectant properties together with CHX [18]. Our results differ from those reported in consulted literature; in our case the average microbial reduction of Listerine was the lowest in comparison to CHX and NaOCl.…”
Section: Discussionmentioning
confidence: 99%